Molecular Profiling of Neprilysin Expression and its Interactions with SARS-CoV-2 Spike Proteins to Develop Evidence Base Pharmacological Approaches for Therapeutic Intervention - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Introduction: Neprilysin due to its peptidase activity is involved in several physiological and pathological processes. Recently our group has reported the association of neprilysin with angiotensin-converting enzyme 2 (ACE2) network proteins which facilitate the entry of SARS-CoV-2 virus. The potential role of neprilysin beyond its peptidase activity is not known. Materials and Methods: Using the established sequence analysis and molecular docking tools, this study evaluated the molecular profile of neprilysin interaction with SARS- CoV-2 virus proteins. Results: Human neprilysin protein showed a significant sequence similarity with SARS-CoV-2 spike protein, which was further confirmed by observation of considerable interaction in the molecular docking. Human neprilysin protein was also found to additionally interact with SARS-CoV-2 proteins facilitating virus replication. The potential of neprilysin inhibitors (Sacubitril and Sacubitrilat) to interfere with neprilysin and SARS-CoV-2 proteins interactions was assessed. The neprilysin inhibitors showed binding efficacy within therapeutically feasible concentration range (1 to 150 uM). Conclusion: This study while reporting a novel role of neprilysin as potential receptor for SARS-CoV-2 virus, highlights the merit in assessing clinical efficacy of neprilysin inhibitors for the management of SARS-CoV-2 infection.
Keywords: Neprilysin; SARS-CoV-2; Receptor pharmacology; Sacubitril; Sacubitrilat; Virus entry